Cultural Value Transmission in Tabu Gong Rede Geda Musical Performances: A Socio-Cultural Analysis - Antonius Harun Ruron; Andi Tenri Juli Astari (Unika Santu Paulus Ruteng, 2025)
This study examines the role of Tabu Gong Rede Geda music as a medium for cultural value transmission in Riangkotek Village, Flores Timur. Using an ethnographic approach, the research reveals that this traditional music serves not only as an artistic expression but also as a means of inheriting spiritual, historical, and social values through an observation-based mentor-apprentice system. Elders act as knowledge custodians, transmitting both musical techniques and the cultural meanings embedded in each performance. The patrilineal social structure and the strong role of customary institutions form the foundation for preserving Tabu Gong Rede Geda. This music functions as a cultural identity marker, a medium for communication with ancestors, and a reinforcement of social cohesion through values of togetherness, responsibility, and spirituality. To ensure its sustainability, strategies such as digital documentation, integration with formal education, and community empowerment are essential. These findings underscore the importance of balancing tradition preservation with innovative adaptation in safeguarding intangible cultural heritage in the era of globalization. These findings highlight the critical need to balance traditional preservation with innovative adaptation in safeguarding this intangible cultural heritage amidst globalization pressures.